Transforming the first-year experience through self and peer assessment - Kearney, Sean (Journal of University Teaching and Learning Practice, 2019)
The transition into higher education from secondary school is a challenging change for many students. This transition and the problems students face as a result, can affect their ability to succeed. Universities recognise the transition to university as a significant feature of student engagement and learning. The current article explores an already established assessment model as a tool to help acculturate first-year students to tertiary assessment practices. The author has moulded a model of self and peer assessment that has been utilised at all levels of schooling, as a specific means to help students engage, not only with content, but also with the administrative processes of assessment. Over the course of a number of weeks, undergraduate education students, in their first semester of university study, were subjected to Authentic Self and Peer Assessment for Learning (ASPAL) model, which sought to illustrate study skills, encourage collaboration, promote autonomy and illustrate to students how assessment can drive learning. The current article presents a case for the use of the ASPAL model of assessment as a transition pedagogy that can help students better understand assessment at the tertiary level and enhance student success.